The Effectiveness of Elderly Management Effort Activities towards Geriatric Depression Scale of Permanent Shelter Residents in Post Eruption of Merapi - Ekorini Listiowati; Warih Andan Puspitosari; Kellyana Kellyana (Intelektual Pustaka Media Utama, 2015)
Disasters can happen due to nature and human being which cause damages, loss, and deteriorating health as well as health care. Psychosocial and mental health problems arise whilst and post disaster since disaster will lead to trauma for those who undergo it. Depression has comorbidity with dementia which decreases the quality of life of the elderly, thus it needs an effective and sustainable treatment with the goal to recover coping mechanism toward physical and psycho-social problem, prevent physical and psycho-social disability, and optimize psycho-social function. The research aimed to analyze the effectiveness of Elderly Management Effort activities towards geriatric depression scale of permanent shelter residents in post Eruption of Merapi. This research is quasi-experimental research using pretest postest design. The subject of this research is 40 people which meet the inclusive criteria: elderly, living in shelter, having non-terminal illnesses, and willing to join the whole research. The exclusive criteria are having a medical record with severe psychological problem and DO which will be used for those who do not join all session completely. The samples were taken using consecutive sampling method. The instruments used in this research are the Geriatric Depression Scale and the Elderly Management Effort. The data were analyzed through t test and chi square. Decreasing of score was found for the Geriatric Depression Scale from 5.2 to 2.1 and back to the score 4.3 at the last intervention in the 10th month. The Elderly Management Effort through the activities in Posyandu including Dance Movement Therapy dan Reminiscence Therapy is proven effective to decrease the Geriatric Depression Scale in post disaster.